Characterization of Antibody Responses to Virus Infections in Humans - Ilinykh, Philipp; Huang, Kai (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on fundamental and applied research on humoral immune responses to viral infections in humans. The comprehensive study of antibody response is critical for the development of diagnostic tools, vaccines, and immunotherapeutics against life-threatening viral infections. Special attention is given to serological surveillance and characterization of virus-neutralizing antibodies.